Pengaruh Minyak dan Ekstrak Tanaman terhadap Perkecambahan Uredospora dan Intensitas Serangan Hemileia vastatrix - Rita Harni; Efi Taufik; Samsudin Samsudin (Jurnal Tanaman Industri dan Penyegar, 2018)
Rust disease caused by fungus Hemileia vastatrix is a major disease of Arabica coffee, which reduces yield by 20%–70%. Botanical fungicide is a potential alternative because environmentally friendly and safe to humans health. The research aimed to analyze the effect of oils and extracts of fungicidal plants on uredospore germination and attack intensity of H. vastatrix. The research was conducted in laboratory and greenhouse of Indonesian Industrial and Beverages Crops Research Institute (IIBCRI), Sukabumi, from January to December 2016. The plant oils were of cloves, citronella, Reutealis trisperma, and neem, while the plant extracts used were mahogany, Ageratum conyzoides, and wood vinegar. Those oils and extracts were assessed on uredospores germination of H. vastatrix, both in vitro and on coffee seedlings in the greenhouse. A complete randomized block design was used with 9 treatments and 5 replications. The oils and extracts at 5% concentration were applied on coffee leaves of 6 months old plants then inoculated with H. vastratrix uredospora simultaneously. Attack symptoms, incubation period, attack percentage and intensity were observed. The results showed that plant oils and extracts used in present study effectively reduced the uredospora germination of H. vastatrix. However, oils of neem and R. trisperma as well as A. conizoides extract are more potential to suppress H. vastatrix infection in coffee leaves in greenhouse and reduced attack intensity from 22.2% to 3.6%; 5.2%; and 7.6% with inhibitory level at 83.8%; 76.6%; and 65.8%, respectively. Therefore, they are considered as potential biocontrols for rust disease.